2022
DOI: 10.3390/metabo12121188
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Egg White Hydrolysate Prevents Male Reproductive Dysfunction after Long-Term Exposure to Aluminum in Rats

Abstract: Aluminum (Al) is a non-essential metal omnipresent in human life and is considered an environmental toxicant. Al increases reactive oxygen production and triggers immune responses, contributing to chronic systemic inflammation development. Here, we have tested whether an egg white hydrolysate (EWH) with potential bioactive properties can protect against changes in reproductive function in rats exposed to long-term Al dietary levels at high and low doses. Male Wistar rats received orally: low aluminum level gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(105 reference statements)
2
1
0
Order By: Relevance
“…A substantial body of research [3,[7][8][9]11,17,27,32,36,[38][39][40][41][42][43] has highlighted a significant increase in aluminum (Al) levels in the testes, epididymis, prostate, seminal vesicles, and bulbo-urethral glands compared to control groups, supporting our findings. However, it is important to note that we did not find studies assessing Al levels in sexual accessory glands for comparison.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A substantial body of research [3,[7][8][9]11,17,27,32,36,[38][39][40][41][42][43] has highlighted a significant increase in aluminum (Al) levels in the testes, epididymis, prostate, seminal vesicles, and bulbo-urethral glands compared to control groups, supporting our findings. However, it is important to note that we did not find studies assessing Al levels in sexual accessory glands for comparison.…”
Section: Discussionsupporting
confidence: 87%
“…However, Martinez et al [40] indicated that while Al impaired testis histology, it did not affect epididymis structure. Their study also noted alterations in body mass, genital organ weight, and sexual accessory gland weight in rats receiving AlCl3 at 100 mg/kg.BW for 60 days.…”
Section: Discussionmentioning
confidence: 97%
“…A substantial body of research [3,[7][8][9]11,17,27,32,36,[38][39][40][41][42][43] has highlighted a significant increase in aluminum (Al) levels in the testes, epididymis, prostate, seminal vesicles, and bulbo-urethral glands compared to control groups, supporting our findings. However, it's important to note that we did not find studies assessing Al levels in sexual accessory glands for comparison.…”
Section: Discussionsupporting
confidence: 87%